The development of multidisciplinary convalescence recommendations after childbirth: a modified Delphi studyAJOG Global Reports at a Glance - Zayël Z. Frijmersum, MD; Eva Van der Meij, MD, PhD; Esther V.A. Bouwsma, MD, PhD; Corine J.M. Verhoeven, PhD; Johannes R. Anema, MD, PhD; Judith A.F. Huirne, MD, PhD; Petra C.A.M. Bakker, MD, PhD (Elsevier, 2024)
BACKGROUND: Evidence suggests that postpartum recovery takes longer than 6 weeks. However, evidence-based recommendations regarding postpartum recovery are lacking. Current research mainly focuses on shortening hospital stay after childbirth, neglecting outpatient recovery. OBJECTIVE: This study aimed to develop multidisciplinary recommendations on convalescence after vaginal and cesarean delivery using a modified Delphi method to improve recovery after childbirth. STUDY DESIGN: Multidisciplinary experts employed in different medical organizations involved in care and guidance of patients during postpartum recovery participated in the study. The panel included 16 experts (5 gynecologists, 2 senior residents, 4 midwives, 2 maternity nurses, 2 general practitioners, and 1 pelvic floor physical therapist) and representatives from medical organizations. Detailed recommendations on convalescence after uncomplicated vaginal delivery and uncomplicated cesarean delivery were developed. In addition, a list with 35 potential affecting factors that could delay recovery was presented to identify circumstances in which the convalescence recommendation should be adapted. Recommendations were based on a literature review and a modified Delphi procedure among 16 experts. Multidisciplinary consensus of at least 67% was achieved on convalescence recommendations for 27 relevant functional activities after childbirth. RESULTS: Multidisciplinary consensus on convalescence recommendations was reached for 26 of 27 functional activities for uncomplicated vaginal and cesarean delivery after 6 Delphi rounds and 2 group discussions. In total, 7 out of 32 affecting factors were deemed as independent factors that may delay recovery and therefore change the convalescence recommendations. The recommendations were deemed feasible by representatives from the same medical organizations as the panel. CONCLUSION: Multidisciplinary consensus on recommendations regarding convalescence after uncomplicated vaginal delivery and uncomplicated cesarean delivery was achieved.